The use of textile-reinforced mortar as a strengthening technique for the infill walls out-of-plane behaviour - Furtado, André (2022)
The primary objective of this work is to present a experimental analysis of textile-reinforced mortar based strengthening solutions to prevent the out-of-plane (OOP) collapse of masonry infills in RC buildings. The experimental campaign comprises the OOP testing of five full-scale infill walls made up of horizontal hollow clay bricks, two of them unstrengthened and the remaining three strengthened, with and without prior damage. All the tests consisted in the application of a semi-cyclic (loading-unloading-reloading) history of imposed displacements in the OOP direction by means of a uniformly distributed load. The mechanical properties of the adopted materials are characterized and presented. The results will be presented in terms of OOP force-displacement responses, deformed shapes, damage evolution, energy dissipation capacity and damping. In the end, the tests’ results are compared to each other to assess the effectiveness of the selected strengthening techniques and to provide a support towards the choice of the best strategies for future further investigations and applications